2019
DOI: 10.1002/eap.2020
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive rangeland management benefits grassland birds utilizing opposing vegetation structure in the shortgrass steppe

Abstract: Rangelands are temporally and spatially complex socioecological systems on which the predominant land use is livestock production. In North America, rangelands also contain approximately 80% of remaining habitat for grassland birds, a guild of species that has experienced precipitous declines since the 1970s. While livestock grazing management may benefit certain grassland bird species by generating the vegetation structure and density they prefer, these outcomes are poorly understood for avian species breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…The effect of grazing has previously been investigated in adaptive management schemes. For example, Davis et al (2020) predicted the effect of different grazing regimes on bird population sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of grazing has previously been investigated in adaptive management schemes. For example, Davis et al (2020) predicted the effect of different grazing regimes on bird population sizes.…”
Section: Discussionmentioning
confidence: 99%
“…If ecosystems are at least partly controllable (i.e., management actions may have positive effects on biodiversity), then a possible societal response to environmental pressures on biodiversity is to manage ecosystems in order to achieve specified conservation goals. However, due to complicated ecosystem dynamics with considerable time lags, the effects of management actions on biodiversity are often uncertain, and it has been recommended to implement adaptive management plans where our uncertainties regarding the ecological processes are taken into account (Williams et al 2009, Westgate et al 2013, Abrahms et al 2017, Fernández-Giménez et al 2019, Davis et al 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rangeland scientists and conservation biologists have described the correlation between heterogeneous vegetation structure and composition of habitat and biodiversity (Tews et al 2004;Knopf and Samson 1997;Davis et al 2019) and to the importance of prairie dogs as keystone species (Sierra-Corona et al 2015) and fire and heavy grazing as key ecological processes in the Western Great Plains (Skagen et al 2018;Derner et al 2009). In contrast to Bement's model (1969) of optimum stocking, the heterogeneity-based paradigm of rangeland ecology (Fig.…”
Section: Response Of the Cared For: The Implications Of Managing For mentioning
confidence: 99%
“…Grazing experiments have demonstrated that patch burn grazing, and grazing on prairie dog colonies, can have limited negative impact on cattle weight gains in the experimental setting (Derner et al 2006), but ranchers often argue that these management practices have negative financial consequences at the ranch scale (one grazing experiments rarely reach, see Sayre 2017). This complexity explains why ranchers may resist the heterogeneity management Knopf and Sampson (1997) and Davis et al (2019). For maximum biodiversity conservation (Fuhlendorf and Engle 2001) and drought resilience (Derner and Augustine 2016;Agrawal 2008), large ungulate grazing would interact with climate, fire and small mammal grazing to create a large spectrum of rangeland structure, thus supporting a suite of grassland bird species.…”
Section: Response Of the Cared For: The Implications Of Managing For mentioning
confidence: 99%